Investigasi Kegagalan Poros Pompa Sentrifugal IP251-U153 pada Unit Recovery Boiler I PT. X - Dedy Masnur; Putri Nawangsari; Dea Musyafiroh Akbar (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2023)
PT. X is one of the industries engaged in the pulp and paper sector which uses centrifugal pumps to move compounds such as liquor, water, and so on. Failure occurred in the operation of the centrifugal pump, namely the fracture of the shaft component which was made of AISI329 stainless steel. This study aims to investigate the failure of the IP251-U153 centrifugal pump shaft and provide recommendations for actions to prevent failure. The stages of analysis carried out were macroscopic analysis of the fracture surface and testing of chemical composition using a Spectral Metal Analyzer. The results of the analysis show that the fracture pattern is brittle intergranular fracture and there is a difference in the percentage chemical composition of the shaft material with the composition of the standard shaft material in the elements Molybdenum (Mo), Manganese (Mn) and Copper (Cu). These elements affect the durability of the shaft. Checking the material composition when accepting a purchase and carrying out a check for alignment on the shaft installation is necessary to avoid failure.